Association between mother's work status and child stunting in urban slums: a cross-sectional assessment of 346 child-mother dyads in Dhaka, Bangladesh (2020) - Hayman Win; Sohana Shafique; Sharmin Mizan; Jordyn Wallenborn; Nicole Probst-Hensch; Günther Fink (BMC, 2022)
Abstract Background A growing literature highlights the increased risk of stunting among children growing up in informal or slum settlements. Despite relatively high rates of female labor force participation in slums, there is limited evidence on relationship between mother's work participation and nutritional outcomes of children in these settings. Methods We conducted a cross-sectional study in two large slums (Korail and Tongi) of Dhaka and Gazipur, Bangladesh to assess the association between maternal work and childhood stunting in a low-income urban context. Logistic regression models estimated unconditional and conditional associations between maternal work status and 1) child stunting, 2) child morbidity and dietary intake, and 3) health and hygiene behaviors. Subgroup analyses were done by type of child care support available. Results After adjusting for variations in individual and household level characteristics, we found that children of working mothers had nearly twice the odds of being stunted than children of non-working mothers (OR 1.84, 95%CI 1.05-3.23). Large differences in stunting were found by available care support: compared to children of non-working mothers, children of working mothers with nuclear-type family support had 4.5 times increased odds of stunting (OR 4.49, 95%CI 1.81-11.12), while no odds differential was found for children of working mothers with an extended-type family support (OR 0.69, 95%CI 0.30-1.59). Conclusions Maternal employment is associated with a substantial increase in the odds of child stunting in the slum areas studied. Given that these effects only appear to arise in the absence of adequate family support, integrating appropriate childcare support measures for low-income urban working mothers might be an effective strategy to help reduce the prevalence of chronic undernutrition among slum children.